2006
DOI: 10.1111/j.1742-4658.2006.05308.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a β‐N‐acetylhexosaminidase and a β‐N‐acetylglucosaminidase/β‐glucosidase from Cellulomonas fimi

Abstract: Most enzymes catalyzing the hydrolysis of terminal b-N-acetylglucosaminide linkages belong to families 3 and 20 of the glycoside hydrolases ([1,2] and the glycoside hydrolases database at URL http://afmb.cnrs-mrs. fr/CAZY/). Members of the two families greatly differ in structure, enzyme mechanism, substrate specificity, and physiologic function (for a review see [3] and references cited therein). The enzymes in family 20 are designated as N-acetylhexosaminidases (EC 3.2.1.52) because they hydrolyze b-N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 46 publications
(75 reference statements)
1
62
0
1
Order By: Relevance
“…For GH3 enzymes, it has been found that the 2-acetamido group of the substrate is not essential for cleavage of the glycosidic bond, consistent with these enzymes using an enzymic nucleophile. 19,27 The X-ray structure of NagZ from Vibrio cholerae (VcNagZ) in complex with its GlcNAc product (PDB entry: 1Y65) corroborates this finding, clearly showing that the 2-acetamido group of bound GlcNAc is not positioned to participate directly in CAO bond cleavage. Crystallographic studies of GH20 human HexA 25 and HexB, 24 and GH84 bacterial homologues of human O-GlcNAcase from Bacteroides thetaiotaomicron (BtGH84) 22 and Clostridium perfringens 26 have revealed that these families of enzymes bind the 2-acetamido group in a strikingly different manner.…”
supporting
confidence: 56%
“…For GH3 enzymes, it has been found that the 2-acetamido group of the substrate is not essential for cleavage of the glycosidic bond, consistent with these enzymes using an enzymic nucleophile. 19,27 The X-ray structure of NagZ from Vibrio cholerae (VcNagZ) in complex with its GlcNAc product (PDB entry: 1Y65) corroborates this finding, clearly showing that the 2-acetamido group of bound GlcNAc is not positioned to participate directly in CAO bond cleavage. Crystallographic studies of GH20 human HexA 25 and HexB, 24 and GH84 bacterial homologues of human O-GlcNAcase from Bacteroides thetaiotaomicron (BtGH84) 22 and Clostridium perfringens 26 have revealed that these families of enzymes bind the 2-acetamido group in a strikingly different manner.…”
supporting
confidence: 56%
“…This modified motif is also present in the only other known glycoside phosphorylase in the GH3 family, Nag3 31,32 . In order to confirm that the activity detected was indeed associated with this gene it was subcloned into a pET expression vector and heterologously expressed and purified.…”
Section: Resultsmentioning
confidence: 92%
“…In both cases the interaction at that position is between an amide and a hydroxyl, but the directionality of the interaction is inverted; a beautiful example of specificity swapping. Indeed, it had previously been speculated that the broadened substrate specificity seen for Nag3, which also prefers glucoside to N-acetylhexosaminide substrates, was due to the substitutions seen in the modified sequence motif 31 :…”
Section: As Seen Inmentioning
confidence: 99%
See 2 more Smart Citations